CHARACTERIZATION OF QUARTZ SAND IN BANGKA REGION AS RAW MATERIAL FOR SOLAR PANELS - Yahya Hidayat, Akmal
Utilization of solar energy as a renewable energy source is becoming an important concern throughout the world. In solar energy, solar radiation is converted into electric current by using solar panels whose raw materials are made of semiconductor materials. The semiconductor material commonly used and obtained is silicon. The presence of silicon in nature is rarely found in its free form, but can be found in the form of silica compounds (SiO2) in quartz minerals. The potential of quartz sand in Indonesia is actually quite abundant, but the use of quartz sand as raw material for solar panels is still not too massive. In this study, the characterization of quartz sand in Bangka area and the possibility of its use as raw material for solar panels was carried out. Quartz sand characterization was carried out using Scanning Electron Microscope (SEM), X-Ray Fluorescence (XRF), and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) analysis. The specification of quartz sand as raw material for solar panels contains silicon dioxide ? 99.7%, iron oxide ? 85 ppm, titanium oxide ? 140 ppm, and aluminum oxide ? 500 ppm. Based on the results of the analysis carried out, samples of quartz sand in Bangka area contain silicon dioxide content of 69.817%–95.604%, iron oxide 11294.63–18014.22 ppm, titanium oxide 131.78–417.03 ppm, and aluminum oxide 2645.3– 17213.35 ppm. Thus, the quartz sand in Bangka area has not met the specifications as raw material for solar panels. Quartz sand in Bangka area still has potential as raw material for solar panels, but it requires a complex and expensive purification process.